Grapevine leaf MALDI-MS imaging reveals the localisation of a putatively identified sucrose metabolite associated to Plasmopara viticola development - Maia, Marisa; McCann, Andréa; Malherbe, Cédric; Far, Johann; Cunha, Jorge; Eiras-Dias, José; Cordeiro, Carlos; Eppe, Gauthier; Quinton, Loïc; Figueiredo, Andreia; De Pauw, Edwin; Sousa Silva, Marta (Frontiers in Plant Science, 2022)
Despite well-established pathways and metabolites involved in grapevine-Plasmopara viticola interaction, information on the molecules involved in the first moments of pathogen contact with the leaf surface and their specific location is still missing. To understand and localise these molecules, we analysed grapevine leaf discs infected with P. viticola with MSI. Plant material preparation was optimised, and different matrices and solvents were tested. Our data shows that trichomes hamper matrix deposition and the ion signal. Results show that putatively identified sucrose presents a higher accumulation and a non-homogeneous distribution in the infected leaf discs in comparison with the controls. This accumulation was mainly on the veins, leading to the hypothesis that sucrose metabolism is being manipulated by the development structures of P. viticola. Up to our knowledge this is the first time that the localisation of a putatively identified sucrose metabolite was shown to be associated to P. viticola infection sites.